Uma análise verbivocovisual dos projetos de dizer sobre o sujeito-louco no documentário Holocausto Brasileiro - Teixeira, Gislaine Aparecida (2022)
Bakhtin Circle theoretical-epistemological bias highlights the constitution of subjects as an alteritarian process [self-other], which supports reflections on the specificities of cultural, temporal and ideological constitution that takes place in formation and recognition of the self, the world and the others. In line with these considerations, the present research aims to discuss, essentially, how the narratives of (and about) the mad-subject are (re)told in documentary films using narrative-evaluative strategies constituted in and by verbivocovisual language (PAULA, 2017), from the alteritarian gaze of the other co-constructor [authorial team]. The focus of the intended discussions is not to reflect on madness as a biological condition, that is, as a mental disorder, but, above all, as a socially constituted place that has, over time, been re-signified. Therefore, the main objective of this study is divided into two major specific objectives: i) investigate how the aesthetic strategies of filmmaking are articulated with the ethical component, as the author team's speech plan is constituted; ii) verify how verbivocovisual utterances participate in the process of narrative alterity in the constitution of these subjects, also bringing together processes of silences – in categories of silence. To do so, the documentary film “Holocausto Brasileiro” (2016) was chosen as the corpus in order to show how the narrative-evaluative choices materialized verbivocovisually in the documentary architect the speech plan of the authorial team and participate in the construction of the documentary's meanings. The theoretical foundation of the research was based, above all, on the works of scholars from Bakhtin Circle (BAKHTIN, 2010; 2017 [1919]; 2017 [1979]; 2019 & VOLÓCHINOV, 2017 [1929]; 2019 [ 1926; 1930]), with the aim of proposing discussions on the concept of utterance, aesthetic architecture and responsible act. Regarding the concepts of cinematographic narrative and the specifics of documentary, Ismail Xavier (2019 [1977]), Fernão Ramos (2008), Robert Stam (2013 [1941]) were chosen, in order to show that representing the past and collectively reconstruct it in a documentary narrative is marked as an ethical/aesthetic positioning of the authorial team. So, it was observed the dialogical and dialectical constitution of the subjects in the madness process and of how certain silences (as signs) constitute this other-place and, consequently, the other-my-place. Therefore, silence assumes, in the present work, four categories proposed and problematized by Villarta-Neder (2019): silence for excess, silence for absence, silence for non-appearance and silence for monument. In summary, it is expected that the analyzes took on in the present work provoke reflections on the constitution of the mad-subject in and through language, demonstrating the discursive ethical character of Bakhtinian philosophy.